100 nm AlSb/InAs HEMT for Ultra-Low-Power Consumption, Low-Noise Applications - Cyrille Gardès; Sonia Bagumako; Ludovic Desplanque; Nicolas Wichmann; Sylvain Bollaert; François Danneville; Xavier Wallart; Yannick Roelens (The Scientific World Journal)
We report on high frequency (HF) and noise performances of AlSb/InAs high electron mobility transistor (HEMT) with 100 nm gate length at room temperature in low-power regime. Extrinsic cut-off frequencies fT/fmax of 100/125 GHz together with minimum noise figure NFmin=0.5 dB and associated gain Gass=12 dB at 12 GHz have been obtained at drain bias of only 80 mV, corresponding to 4 mW/mm DC power dissipation. This demonstrates the great ability of AlSb/InAs HEMT for high-frequency operation combined with low-noise performances in ultra-low-power regime.